PEMBUATAN APLIKASI TRUE PARENTING PERSONALITY TEST UNTUK VISUALISASI TES KEPRIBADIAN - Evan Tanazal; Endah Asmawati; Melissa Angga (CALYPTRA, 2018)
TPPT personality test participants often have trouble interpreting their test questions and results. That’s why its requires explanation for participants to make it easier to understand their questions and results of their personality test. To overcome these problems, an android-based TPPT application was created, it has an explanation and understanding of test and test results in the form of video. After implementation and verification, the application is in accordance with the design and error free. Based on the validation data it is known that the application has been able to help explain to TPPT participants to understand and know their personality.